Will China Remain a Top Player in the International Education Market? - Zha, Qiang (International Higher Education, 2022)
Chinese students are still motivated to study abroad, yet, in five years or so, their motivations might weaken. This is primarily due to economic slowdown, changing domestic conditions, and geopolitical decoupling.